2021
DOI: 10.1108/jcefts-09-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Do institutional risk preferences exist in Chinese direct investments in ASEAN countries? A case study of Chinese-funded enterprises in Laos

Abstract: Purpose Institutional factors play an important and complex role in Chinese outward foreign direct investment (OFDI) location choices that do not seem to be influenced by a host country’s high political risks. Moreover, the location choice for OFDI is key to corporate strategic decision-making on internationalization. Therefore, this study aims to examine the direct investments of Chinese multinational enterprises (MNEs) in Laos. Design/methodology/approach Combining the purposive sampling strategy and snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Wang et al, 2021). Additionally, Chinese enterprises are more willing to invest in countries whose institutional quality level is closer to Chinas’ to better adapt to investment environment (S. Chen et al, 2021; De Beule & Zhang, 2022).…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al, 2021). Additionally, Chinese enterprises are more willing to invest in countries whose institutional quality level is closer to Chinas’ to better adapt to investment environment (S. Chen et al, 2021; De Beule & Zhang, 2022).…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Wang et al, 2021). Additionally, Chinese enterprises are more willing to invest in countries whose institutional quality level is closer to Chinas' to better adapt to investment environment (S. Chen et al, 2021;De Beule & Zhang, 2022). Moreover, Zhao (2022) revealed that institutional quality improvement may play a significant role in hindering Chinese OFDI spillover effect, and Chinese OFDI spillover effect is more obvious in B&R countries with weak institutional quality (Such as Southeast Asia and West Asia regions).…”
Section: Analysis Of the Role Of Bandr Countries' Institutional Quali...mentioning
confidence: 99%